2018
DOI: 10.1007/s13555-018-0266-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Risk Factors Associated with Psoriatic Arthritis among Patients with Psoriasis

Abstract: IntroductionPsoriatic arthritis (PsA) is a chronic, inflammatory arthritis that affects an estimated 30% of patients with psoriasis. PsA is underdiagnosed in primary care and dermatology clinics due to a variety of reasons, including failure of healthcare providers to ask about symptoms, overlap of symptoms and signs with other rheumatologic conditions, and lack of a specific diagnostic test. A delay in PsA diagnosis and treatment, even as short as 6 months, can lead to decreased quality of life, increased joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
(33 reference statements)
4
27
1
1
Order By: Relevance
“…21 Furthermore, a weighted model that only included HLA risk alleles was found to be the best discriminator of all the models tested, which also supports literature asserting the driving force of certain HLA risk alleles in the development of PsA. [20][21][22] Future efforts are aimed in 3 directions. First, recently published data demonstrates the advantages of using large cohorts and a high number of genetic markers (ie, 200 risk alleles) to identify subtle genetic differences that better distinguish PsA from PsO.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…21 Furthermore, a weighted model that only included HLA risk alleles was found to be the best discriminator of all the models tested, which also supports literature asserting the driving force of certain HLA risk alleles in the development of PsA. [20][21][22] Future efforts are aimed in 3 directions. First, recently published data demonstrates the advantages of using large cohorts and a high number of genetic markers (ie, 200 risk alleles) to identify subtle genetic differences that better distinguish PsA from PsO.…”
Section: Resultssupporting
confidence: 75%
“…HLA genes are unique in that they code for cell surface antigen proteins responsible for major functions of the immune system. The role of HLA genes in PsA risk is well-documented, 20,21,22 suggesting that an HLA-only PsA GRS could capture a significant proportion of the genetic contribution to developing this disease.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of nail involvement in our study population is lower than that observed in previous real-world studies of patients with varied prior biologic experience, which have reported rates of nail involvement ranging from 50% to 87% among patients with PsA. (33)(34)(35)(36)(37)(38)(39) Notably, approximately 31% of patients in our study population had received biologic therapy and 29% had received conventional synthetic disease-modifying antirheumatic drugs prior to enrollment, which may have ameliorated nail disease in those patients before their participation in the study. (5,26) Additionally, the majority of previous studies specifically enrolled patients with PsA and psoriasis, whereas the presence of psoriasis was not a criterion for enrollment in our study.…”
Section: Discussioncontrasting
confidence: 64%
“…The SNP data used in the construction of the reference panel for this study was drawn from two sources, both reported in previous studies: "UCSF" (Yan et al, 2018) and "University of Dundee" (Nititham et al, 2018).…”
Section: Snp Datamentioning
confidence: 99%